...THE PUBLIC UTILITY HOLDING COMPANY... (The Accounting Review, 1932)
Two decades ago a public utility investment holding company was established in Chicago under the laws of the State of Delaware with an initial issued capital of $12,000,000. The company had acquired a controlling interest in 54 major public utility holding and operating companies in many sections of the United States and Canada, and had invested heavily in others with which affiliation existed through allied managements. In September, 1929, the company went through a complete recapitalization, during the process of which 4,777,270 new shares of its common stock were sold to the public at $20 a share, while 8,700,720 of the new common shares were issued in exchange for a corresponding amount of old common which had a paid-in value not in excess of $10 a share. During 1980 and 1981 certain loans were made to subsidiary companies for the purpose of enabling them to meet their dividend and interest payments. In this manner the company loaned money and immediately retrieved it as income.